2000
DOI: 10.1046/j.1525-1446.2000.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Problems and Advanced Practice Nurse Interventions During Transitional Care

Abstract: This study is a secondary analysis of patient records written by advanced practice nurses (APNs) as they provided discharge planning and 4 weeks of home follow-up to elderly patients hospitalized with common medical and surgical conditions. The purposes of this study were to examine the problems experienced by elders who were hospitalized and discharged to home, the interventions used by APNs as they cared for these patients, and the linkages between patient problems and APN interventions. Care logs written by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 24 publications
(25 reference statements)
0
56
0
3
Order By: Relevance
“…In this study, health care supervision was documented as a problem for every patient, which validates the rationale for engaging DP staff to coordinate care in the transition to home-based care services. In contrast, Bowles (2000b) and Naylor et al (2000) found the most frequent problems to be in the physiological domain. No physiological problems were addressed by DP staff in our study, which may be explained by the division of DP responsibilities across numerous members of the health care team at the study site.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…In this study, health care supervision was documented as a problem for every patient, which validates the rationale for engaging DP staff to coordinate care in the transition to home-based care services. In contrast, Bowles (2000b) and Naylor et al (2000) found the most frequent problems to be in the physiological domain. No physiological problems were addressed by DP staff in our study, which may be explained by the division of DP responsibilities across numerous members of the health care team at the study site.…”
mentioning
confidence: 71%
“…Each clinical note was printed and placed in a binder for coding and review by the study team. Previous studies testing the Omaha System using DP notes demonstrated the feasibility of coding nearly 100% of text phrases to Omaha System problems and interventions (Bowles, 2000a andNaylor et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations